Senegal : Fiscal Transparency Evaluation. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2019)
This paper discusses results of a fiscal transparency evaluation (FTE) in Senegal. This evaluation puts forward a number of recommendations that would enable Senegal to continue to improve its fiscal transparency while strengthening the fiscal risk management framework. The recommendations relate to five objectives and are accompanied by an Action Plan. Practical examples have been included in the report to back the various recommendations and facilitate their implementation. The paper also highlights that fiscal reporting practices in Senegal can be improved in light of the IMF's Fiscal Transparency Code. It has been observed that the fiscal and accounting reforms undertaken in the past few years can be expected to enhance fiscal transparency in the medium term. Project appraisal and selection mechanisms have recently been revamped and there is now more information regarding their feasibility available to the general public. The FTE finds that Senegal is positioned at the average level for countries of similar income and institutional capacity.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet